Letter to the Editor: To the John Bates Clark Medal Committee - Benno Torgler (Open Economics, 2019)
This humoristic piece pretends to offer a candidacy for the John Bates Clark Medal.
Keywords: 330; Economics of Science; Humour; John Bates Clark Medal